2017
DOI: 10.1016/j.molmet.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Inducible overexpression of adiponectin receptors highlight the roles of adiponectin-induced ceramidase signaling in lipid and glucose homeostasis

Abstract: ObjectiveAdiponectin and the signaling induced by its cognate receptors, AdipoR1 and AdipoR2, have garnered attention for their ability to promote insulin sensitivity and oppose steatosis. Activation of these receptors promotes the deacylation of ceramide, a lipid metabolite that appears to play a causal role in impairing insulin signaling.MethodsHere, we have developed transgenic mice that overexpress AdipoR1 or AdipoR2 under the inducible control of a tetracycline response element. These represent the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 39 publications
3
139
0
1
Order By: Relevance
“…Despite decreased hepatic triglycerides, hepatic DAG concentrations were reported to be increased in the transgenic mice — an unusual dissociation [61]. Similar findings of protection from hepatosteatosis and hepatic insulin resistance in association with decreased hepatic ceramides were recently reported in mice with adipose- or liver-specific inducible adiponectin receptor overexpression [96]. In summary, mouse models of altered ceramide synthesis appear to develop complex and sometimes dramatic changes in hepatic lipids.…”
Section: Ceramides In Hepatic Insulin Resistancesupporting
confidence: 56%
“…Despite decreased hepatic triglycerides, hepatic DAG concentrations were reported to be increased in the transgenic mice — an unusual dissociation [61]. Similar findings of protection from hepatosteatosis and hepatic insulin resistance in association with decreased hepatic ceramides were recently reported in mice with adipose- or liver-specific inducible adiponectin receptor overexpression [96]. In summary, mouse models of altered ceramide synthesis appear to develop complex and sometimes dramatic changes in hepatic lipids.…”
Section: Ceramides In Hepatic Insulin Resistancesupporting
confidence: 56%
“…This is consistent with our recent observations that APN receptor overexpression in liver or adipose tissue triggers rapid reductions in tissue and plasma ceramide levels. These effects of the receptors are strictly dependent on the presence of APN [7]. Furthermore, recent structural insights into the APN receptors point directly at a receptor-inherent ceramidase activity and further highlights the sphingolipid axis as a major primary mediator of APN effects [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Although profound beneficial metabolic effects of gain-of-function Adipoq (encoding APN) models have been demonstrated through both the Δgly model and, more recently, overexpression of APN receptors [6, 7], loss-of-function models of Adipoq have had varying outcomes regarding metabolic phenotype. Studies by Kubota et al and Maeda et al showed mild-to-moderate insulin resistance and glucose intolerance in APN-deficient mice [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In the liver, adiponectin improves insulin sensitivity with an accompanying reduction in gluconeogenesis. In addition, work from Holland and colleagues revealed a direct role for adiponectin signaling in regulation of cellular ceramide levels (184, 185). These in vitro and in vivo studies revealed that both AdipoR1 and AdipoR2 exhibit ceramidase activity that is enhanced by adiponectin and reduces cellular ceramide concentration (184, 185).…”
Section: Adiposity and Insulin Resistancementioning
confidence: 99%
“…In addition, work from Holland and colleagues revealed a direct role for adiponectin signaling in regulation of cellular ceramide levels (184, 185). These in vitro and in vivo studies revealed that both AdipoR1 and AdipoR2 exhibit ceramidase activity that is enhanced by adiponectin and reduces cellular ceramide concentration (184, 185). Consistent with these data, crystal structures of both AdipoR1 and AdipoR2 suggest they possess intrinsic ceramidase activity (487).…”
Section: Adiposity and Insulin Resistancementioning
confidence: 99%